Pengaruh Media Pembelajaran WordWall terhadap Motivasi dan Hasil Belajar Siswa pada Materi Sistem Ekskresi Kelas XI SMA Negeri 23 Makassar - Muh. Risal; Muhammad Wajdi; Riza Sativani Hayati (Mataram University, 2026)
This study aimed to determine the effect of using WordWall learning media on students’ motivation and learning outcomes in the excretory system topic among eleventh-grade students at SMA Negeri 23 Makassar. The study employed a quasi-experimental method with a nonequivalent control group design. The research population consisted of all Grade XI students, while the sample included Class XI Merdeka 2 as the experimental group and Class XI Merdeka 1 as the control group, selected through purposive sampling. Data were collected using tests, questionnaires, and documentation. The data were analyzed using descriptive and inferential statistics. The results showed that students’ learning motivation in the experimental class was higher than that in the control class. The Mann–Whitney test yielded a significance value of 0.000 < 0.05, indicating a significant effect of WordWall media on students’ learning motivation. In terms of learning outcomes, the experimental class also demonstrated greater improvement than the control class, with an N-Gain score of 0.71 in the high category, while the control class obtained an N-Gain score of 0.53 in the moderate category. The independent sample t-test produced a significance value of 0.009 < 0.05, indicating a significant effect of WordWall learning media on students’ learning outcomes. Therefore, it can be concluded that the use of WordWall learning media has a positive and significant effect on students’ motivation and learning outcomes in the excretory system topic.